O vremeni i o sebe. Anna Akhmatova . O vremeni i o sebe. Anna Akhmatova . Time and Personality. Anna Ahmatova . О времени и о себе. Анна Ахматова - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Poetic anthology devoted to the life and works of Anna Akhmatova. Featured in the program: Demidova, Alla Sergeevna (Reader) Поэтическая антология посвящена жизни и творчеству Анны Ахматовой. В программе участвуют: Демидова, Алла Сергеевна (Чтица)